Percepción social del servicio de agua potable en zonas críticas del distrito de Punchana. Región Loreto. 2019 - Luca Cachique, Roy Franco Segundo (2021)
The objectives pursued with this work is to evaluate the social perception of the drinking water service in critical areas of the District of Punchana, in terms of continuity, water quality, frequency of shortages, as well as knowing the conditions of supply of housing. , presence of storage infrastructure, cleanliness of it. The data collection was carried out between the months of January to February 2019, through visits and the application of a face-to-face survey with the residents of the study area. to the study communities. Drinking water users supplied by tanker trucks rate the service as regular and usually have a discontinuous service. Users quote for this service at the SEDALORETO offices (83.23%), however, they do not know the volume of water for which they pay. The service frequency is every 2 days (72.22%). Drinking water is treated and purchased from different companies dedicated to this area (94.44%). They consider the quality of the water from normal (72.22%) to good (27.78%) and only particles settled in the containers in which the water is stored are observed. This water is destined for different domestic services. The monthly payment is between S /. 20 and 40, many say they do not agree with this due to the frequency of the service (55.56%). They do not present water diseases resulting from the intake of contaminated water (77.78%). They suggest expanding the distribution of the drinking water network that covers all districts (55.56%) as well as avoiding contamination of rivers. The negative feelings towards the water service that were expressed by the respondents are anger or frustration (66.68%) and none (22.22%).